2016
DOI: 10.1039/c6ra04500f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of nalidixic acid degradation by clinoptilolite nanorod-catalyzed ozonation process

Abstract: The removal of nalidixic acid (NAD) through the clinoptilolite nanorod (CN)-catalyzed ozonation process was modeled by three types of kinetic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Recently, theoretical and experimental investigations on porous graphene [36][37][38][39][40][41][42], graphitic carbon nitride [43][44][45], graphdiyne [46,47], bonded porous graphene (BPG) [48] and other 2D materials [49][50][51][52] with high stability and subnanometer-sized pores for gas separation have been intensively carried out. In a density functional theory (DFT) study, Jiang et al [36] designed a porous graphene nanosheet with nitrogen-edged pores and showed its high efficiency for H 2 / CH 4 separation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, theoretical and experimental investigations on porous graphene [36][37][38][39][40][41][42], graphitic carbon nitride [43][44][45], graphdiyne [46,47], bonded porous graphene (BPG) [48] and other 2D materials [49][50][51][52] with high stability and subnanometer-sized pores for gas separation have been intensively carried out. In a density functional theory (DFT) study, Jiang et al [36] designed a porous graphene nanosheet with nitrogen-edged pores and showed its high efficiency for H 2 / CH 4 separation.…”
Section: Introductionmentioning
confidence: 99%